Mastering the complex sale - Jeff Thull, (JOHN WILEY & SONS, INC., 2003)
The businesses we sell to, the problems we solve, and the solutions we offer have evolved tremendously in the past 50 years. This raises a few questions: â€œCan you, as a salesperson, a manager, or an organization, effectively compete in todayâ€™s market?â€ The fact is, a high percentage of salespeople and the organizations they work for havenâ€™t kept pace with this evolution. Weâ€™re living and working in a time Iâ€™ve come to refer to as â€œthe third era of selling.â€ Understanding the history of this evolution is an important factor to moving forward into Era 3. So let me step back with you for a moment. Several years ago, I was asked to teach a course in Instructional Design, at the University of Minnesota, as it relates to â€œSales Training.â€ As the instructor, you are obligedâ€”in any introductory courseâ€”to work a short â€œHistory of This Disciplineâ€ speech into the first class session. As I surveyed what literature there was on the subject, I found that sales, unlike most other functions in the modern corporation, didnâ€™t really have much of a â€œhistory.â€ At least, nobody studied and wrote about selling in the same way that they studied and wrote about Marketing, Logistics, Quality, Operations, or General Management. Even Purchasing has a longer academic pedigree than Sales.